The Use of Non-Verbal Communication to Improve the Ability to Memorize Surah Al-Ikhlas in Class II Students of MI DDI Teppo Pinrang - Sarifah, Sarifah; Firman, Firman; Muhammadun, Muzdalifah (IAIN Parepare, 2021)
This article discusses the use of non-verbal communication to improve the ability to memorize Surah al Ikhlas in Class II students of MI DDI Teppo Pinrang. This study aims to determine the use of non-verbal communication to improve the ability to memorize surah al Ikhlas in Class II students of MI DDI Teppo, Pinrang Regency. The type of research used in this research is Classroom Action Research or Classroom Action Research (PTK). The location of this research is MI DDI Teppo Pinrang Regency. The results showed, a) Steps to improve the ability to memorize surah al ikhlas for class II students of MI DDI Teppo, Pinrang Regency through the use of non-verbal communication which includes body movements ( kinesthetic ), facial expressions and other gestures ( body image ). b) The results of the application of non-verbal communication in improving the ability to memorize surah al Ikhlas for students in Class II MI DDI Teppo Pinrang have been successful and have increased. This can be proven by the acquisition of an average value in each cycle that has increased, namely cycle I of 6.34, then cycle II of 7.5, and cycle III of 8.54. c) Ability to memorize surah al Ikhlasin students through using non-verbal communication experienced a significant increase from the acquisition of the average value in each cycle. The use of non-verbal communication is effective in improving the ability to memorize surah al Ikhlas in class II students of MI DDI Teppo, Pinrang Regency.